Evaluation of focused multipolar stimulation for cochlear implants: a preclinical safety study - Shepherd, Robert; Wise, Andrew; Enke, Ya Lang; Carter, Paul; Fallon, James (IOP Publishing Ltd, 2017)
OBJECTIVE: Cochlear implants (CIs) have a limited number of independent stimulation channels due to the highly conductive nature of the fluid-filled cochlea. Attempts to develop highly focused stimulation to improve speech perception in CI users includes the use of simultaneous stimulation via multiple current sources. Focused multipolar (FMP) stimulation is an example of this approach and has been shown to reduce interaction between stimulating channels. However, compared with conventional biphasic current pulses generated from a single current source, FMP is a complex stimulus that includes extended periods of stimulation before charge recovery is achieved, raising questions on whether chronic stimulation with this strategy is safe. The present study evaluated the long-term safety of intracochlear stimulation using FMP in a preclinical animal model of profound deafness. APPROACH: Six cats were bilaterally implanted with scala tympani electrode arrays two months after deafening, and received continuous unilateral FMP stimulation at levels that evoked a behavioural response for periods of up to 182 d. Electrode impedance, electrically-evoked compound action potentials (ECAPs) and auditory brainstem responses (EABRs) were monitored periodically over the course of the stimulation program from both the stimulated and contralateral control cochleae. On completion of the stimulation program cochleae were examined histologically and the electrode arrays were evaluated for evidence of platinum (Pt) corrosion. MAIN RESULTS: There was no significant difference in electrode impedance between control and chronically stimulated electrodes following long-term FMP stimulation. Moreover, there was no significant difference between ECAP and EABR thresholds evoked from control or stimulated cochleae at either the onset of stimulation or at completion of the stimulation program. Chronic FMP stimulation had no effect on spiral ganglion neuron (SGN) survival when compared with unstimulated control cochleae. Long-term implantation typically evoked a mild foreign body reaction proximal to the electrode array; however stimulated cochleae exhibited a small but statistically significant increase in the tissue response. Finally, there was no evidence of Pt corrosion following long-term FMP stimulation; stimulated electrodes exhibited the same surface features as the unstimulated control electrodes. SIGNIFICANCE: Chronic intracochlear FMP stimulation at levels used in the present study did not adversely affect electrically-evoked neural thresholds or SGN survival but evoked a small, benign increase in inflammatory response compared to control ears. Moreover chronic FMP stimulation does not affect the surface of Pt electrodes at suprathreshold stimulus levels. These findings support the safe clinical application of an FMP stimulation strategy.
Keywords: Cochlear implant; Neural prosthesis; Electrical stimulation; Preclinical safety